Evaluation of Langerhans cells counts comparing HIV-positive and negative anal squamous cell-carcinoma patients - Cruz,Sylvia Heloisa Arantes (2012)
PURPOSE: To investigate the differences in Langerhans cells (LCs) populations between HIV-positive and negative anal squamous cell carcinomas patients. METHODS: Twenty five patients (14 HIV-positive and 11 HIV-negative) were evaluated. Paraffin-block transversal thin sections from biopsies of anal squamous cell carcinomas (ASCC) were stained using the anti-CD1A antibody that identifies activated LCs. LCs counts were performed using histometry at 20 different sites, at baseline in the ASCC cases. These were then compared with LCs counts in anal canal specimens from HIV-negative and positive patients without ASCC (controls groups). RESULTS: In patients with ASCC, the LC count was greater among HIV-negative individuals than among HIV-positive individuals (p<0.05). The LC count was greater in the control HIV-negative group than in HIV-positive patients with ASCC (p<0.05). CONCLUSION: There was a lower amount of activated LCs in HIV-positive patients with anal squamous cell carcinomas than in HIV-negative patients, thereby suggesting worsening of the immune response.